2020
DOI: 10.1108/jpbm-07-2019-2481
|View full text |Cite
|
Sign up to set email alerts
|

Will college students take a stand? Effects of health orientations on purchase decision factors for standing desks

Abstract: Purpose This study aims to examine the impact of college students’ health and wellness orientations on the perceived importance of health benefits for an innovative new brand of standing desk, which is hypothesized to positively affect students’ attitudes and intentions. Research in this domain for the college student market is sparse. Design/methodology/approach An online survey was conducted among business students at a large Midwestern US University, with class credit offered for completion. Of the 325 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 107 publications
0
1
0
1
Order By: Relevance
“…Thus, H 2 was rejected. Previous studies often discussed the relationship between health motivation and behavioral intention; certain studies suggested a positive relationship between health motivation and behavioral intention ( 8 , 73 ). Several other studies reported different findings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, H 2 was rejected. Previous studies often discussed the relationship between health motivation and behavioral intention; certain studies suggested a positive relationship between health motivation and behavioral intention ( 8 , 73 ). Several other studies reported different findings.…”
Section: Discussionmentioning
confidence: 99%
“…Secara konseptual, manfaat fungsional diartikan sebagai nilai ekonomi yang diperoleh perorangan (Su, et al, 2022). Manfaat fungsional memiliki kaitan yang erat dengan kualitas produk serta kualitas layanan yang diberikan, fleksibilitas an daya respon, serta harga produk (Goodrich, Benden, Munch, & Wamwara, 2020). Selain itu, manfaat fungsional berkaitan dengan nilai moneter yang dibandingkan dengan alternatif pilihan produk lainnya (Rizkitysha & Hananti, 2022).…”
Section: Functional Benefitunclassified